Evolving concepts in HER2 evaluation in breast cancer: Heterogeneity, HER2-low carcinomas and beyond. (July 2021) - Marchiò, Caterina; Annaratone, Laura; Marques, Ana; Casorzo, Laura; Berrino, Enrico; Sapino, Anna
Abstract: The human epidermal growth factor receptor 2 (HER2) is a well-known negative prognostic factor in breast cancer and a target of the monoclonal antibody trastuzumab as well as of other anti-HER2 compounds. Pioneering works on HER2-positive breast cancer in the 90s' launched a new era in clinical research and oncology practice that has reshaped the natural history of this disease. In diagnostic pathology the HER2 status is routinely assessed by using a combination of immunohistochemistry (IHC, to evaluate HER2 protein expression levels) and in situ hybridization (ISH, to assess HER2 gene status). For this purpose, international recommendations have been developed by a consensus of experts in the field, which have changed over the years according to new experimental and clinical data. In this review article we will document the changes that have contributed to a better evaluation of the HER2 status in clinical practice, furthermore we will discuss HER2 heterogeneity defined by IHC and ISH as well as by transcriptomic analysis and we will critically describe the complexity of HER2 equivocal results. Finally, we will introduce the clinical impact of HER2 mutations and we will define the upcoming category of HER2-low breast cancer with respect to emerging clinical data on the efficacy of specific anti-HER2 agents in subgroups of breast carcinomas lacking the classical oncogene addition dictated by HER2 amplification.